The new Sonoma diet : trimmer waist, more energy in just 10 days - Guttersen, Connie. frey50 (New York : Sterling, 2010)
Presents a diet plan based on the cuisines of the Mediterranean and Californian wine country and includes detailed menus; new recipe ideas for family, gluten-free, and on-the-go meals; and breakthrough nutrition science.
"A simple, healthy, more delicious way to live."
Keywords: Reducing diets; Weight loss